2020
DOI: 10.15282/ijim.8.0.2020.5759
|View full text |Cite
|
Sign up to set email alerts
|

Review Paper: The Mediating Role of Creativity on the Relationship Between Knowledge Management and Human Resource Management Toward Innovation Performance in the Jordanian Smes

Abstract: This study aims to review around 100 previous studies in the SMEs in Jordan. The economic revolution at the current moment is relying on the SMEs industry to handle the crucial business in the countries. The main concern of this study is the innovation performance in the SMEs in Jordan, which is a need to compete in the current competitive business world nowadays. This study found the innovation performance is needed in the SMEs in Jordan. The study found human resource management, knowledge management, and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Hadiyati and Hendrasto (2021) added that in this Covid-19 pandemic era, reliable, knowledgeable human resources are key because they provide creative and innovative ideas for a small business to survive and grow (Hadiyati & Hendrasto, 2021). This was also confirmed again by Abdulaal and Nordin (2020) who found that creativity and innovation can be expected from quality human resources, (Abdulaal & Nordin, 2020). Bilan et al (2020) found that good human resources are an important and effective factor in the growth of SMEs, especially in increasing sales revenue, enterprise assets, and expansion volume (Bilan, Mishchuk, Roshchyk, & Joshi, 2020).…”
Section: Explanation : Column C Refers To Religious Figurinementioning
confidence: 86%
“…Hadiyati and Hendrasto (2021) added that in this Covid-19 pandemic era, reliable, knowledgeable human resources are key because they provide creative and innovative ideas for a small business to survive and grow (Hadiyati & Hendrasto, 2021). This was also confirmed again by Abdulaal and Nordin (2020) who found that creativity and innovation can be expected from quality human resources, (Abdulaal & Nordin, 2020). Bilan et al (2020) found that good human resources are an important and effective factor in the growth of SMEs, especially in increasing sales revenue, enterprise assets, and expansion volume (Bilan, Mishchuk, Roshchyk, & Joshi, 2020).…”
Section: Explanation : Column C Refers To Religious Figurinementioning
confidence: 86%
“…In the Jordanian context, Abdulaal and Nordin [59] found that knowledge management, human resource management, and innovativeness must be included in the SMEs culture to assist the nation's economy, environment, and society. Likewise, Al-Abbadi et al [60] investigated the effects of entrepreneurial orientations and the performance of Jordanian SMEs, their findings suggested that SMEs should create solid networks and consider unique strategic alliances to create sustainability and competitive advantage.…”
Section: Figure 1 a Proposed Conceptual Model Of Strategic Entreprene...mentioning
confidence: 99%